An Independent Seizure-Onset Zone in Medial Temporal Lobe Found by 18F-FDG PET Imaging Besides Epileptogenic Periventricular Nodular Heterotopia. (27th September 2022) - Guo, Ruijie; Jin, Liri; Dou, Wanchen; Liu, Linwen; Cui, Ruixue
Abstract: A 23-year-old man with drug-resistant epilepsy was admitted for presurgical evaluation. The epileptogenic zone could not be derived from seizure semiology and scalp electroencephalographic monitoring definitely. MRI showed periventricular nodular heterotopia in occipital horn of left lateral ventricle with high FDG uptake on interictal 18 F-FDG PET scan, whereas the hypometabolic zone in the left medial temporal lobe was also found on PET with no abnormality on MRI. Stereoelectroencephalographic implantation was performed to identify the seizure-onset zone. Two independent epileptogenic foci located in periventricular nodular heterotopia and left hippocampus were validated by stereoelectroencephalographic monitoring and the outcome of subsequent thermocoagulation.